Wplyw dlugotrwalego intensywnego wysilku na stezenia we krwi aldosteronu, kortyzolu, testosteronu i niektóre parametry biochemiczne - Przyylski, J.; Zaborniak, S.; Obodynski, K.; Drozd, S.; Garmulewicz, M. (Medycyna sportowa, 2000)
In 8 highly fit subjects biochemical and hormonal examinations were conducted before and after having run 20 km. Blood was withdrawn before the run (0) and after the run: 2-3 min (1), 30 min (2), 4 h (3) and 24 h (4). The following assays were carried out: hematocrit, total and bound bilirubin, activities of aspartic (AspAT) and alanine (AlAT) aminotransferases and of creatine kinase (CK), concentrations of sodium, potassium, cortisol, aldosterone and testosterone. The concentrations of hormones were corrected for changes in plasma volume (from hematocrit). Plasma volume significantly decreased just after the run and steadily increased thereafter reaching significantly higher values in time points 3 and 4. No significant changes were observed for sodium concentration while that of potassium increased slightly but significantly in time points 1 and 3. On the other hand, total contents of sodium and potassium significantly decreased immediately after the run but then significantly increased in time points 3 and 4. Activities of aminotransferases were within normal limits throughout the study but in time points 1-4 (AspAT) or 2 and 4 (AlAT) were significantly higher from the resting ones. No significant changes in bilirubin were observed. Mean activity of CK was steadily, significantly increasing starting 30 min post-run. Mean concentrations of cortisol and aldosterone significantly increased in time points 1 and 2. However, those values were in two subjects slightly lower in those time points and decreased thereafter still further. No significant changes were observed for testosterone concentrations.